An investigation of the ways in which public health nutrition policy and practices can address climate change - Sulda, Heidi; Coveney, John; Bentley, Michael (Public health nutrition, 2010)
To develop a framework to guide action in the public health nutrition workforce to develop policies and practices addressing factors contributing to climate change. Action/consultative research. Interviews - South Australia, questionnaire - Australia. Interviews - key informants (n 6) were from various government, academic and non-government positions, invited through email. Questionnaire - participants were members of the public health nutrition workforce (n 186), recruited to the study through emails from public health nutrition contacts for each State in Australia (with the exception of South Australia). Support by participants for climate change as a valid role for dietitians and nutritionists was high (78 %). However, climate change was ranked low against other public health nutrition priorities. Support of participants to conduct programmes to address climate change from professional and work organisations was low. The final framework developed included elements of advocacy/lobbying, policy, professional recognition/support, organisational support, knowledge/skills, partnerships and programmes. This research demonstrates a need for public health nutrition to address climate change, which requires support by organisations, policy, improved knowledge and increased professional development opportunities.